Kinetic and electrochemistry teaching-learning using experimental activities: case study in higher education (Research, Society and Development, 2020)
The teaching of chemistry generates among students a feeling of discomfort due to the difficulties existing in the teaching-learning process and often the teachers are not prepared to act in an interdisciplinary way. Given the difficulties, it is necessary to search for teaching methodologies that approach the subject in a contextualized way and attract the attention of students. In this regard, the author sought to develop a contextualized teaching proposal, through practical experiment, that would address the themes of corrosion and kinetics, with the aim of developing critical thinking in students. In this context, the present work aimed to present a “Case Study” methodology through experimental observation of corrosion of galvanized and non-galvanized steel clamp in different electrolytic solutions and thus find the order of corrosion reaction by speed integration laws. The research would be qualitative and quantitative, as it shows the contribution of experimental observations to the teaching-learning process by addressing the kinetics and corrosion contents, as well as finding the corrosion rate and reaction order. Students showed that the type of electrolyte influences the corrosion velocity. Non-galvanized clamps are more susceptible to corrosion when using NaOH solution. The NaCl solution is relatively weak to corrode the clamp, and in an acidic aqueous medium the clamp corrosion rate is higher. Corrosion of the clamp in different electrolyte solutions follows as a zero order reaction.